Work In Progress: Comparison research between Spain and Portugal's touristic SME Family firms about open innovation attitudes. - Soler-Porta, Mariano; Padilla-Meléndez, Antonio; Rodríguez-Díaz, Beatriz (My University, 2023)
Once the characteristics of Family Businesses have been studied and evidence found in the literature on the good suitability of open innovation for this type of company, we propose a study in which we will carry out qualitative research on this type of company. This study will be carried out in family businesses in the tourism sector where we will find out the opinion of these companies, through their managers, on the characteristics that are usually described in the literature on Family Businesses and on the application of open innovation. to make changes in companies. It will be carried out in a comparative way in Spain and Portugal in order to determine if there is also a social and cultural component in the opinions obtained from these companies.
Keywords: Turismo - Gestión; Family Firms; Open innovation; Comparative research